Professores universitários: análise dos efeitos de um curso a distância na sensibilização quanto aos cuidados com a voz - Jeronimo, Thamiris Pereira Fonseca (2023)
INTRODUCTION: few studies analyze actions performed with university professors. These are part of a group that presents complaints and vocal disorders and the offer of workshops in distance modality can be a strategy for the promotion of vocal health of this teacher. OBJECTIVE: to analyze the effects of the course "Professor, let's take care of your voice", offered as a distance learning modality in order to sensitize university professors about the care with their voice and the factors of the environment and work organization that interfere with voice production. METHODS: observational, cross-sectional, descriptive comparative research before and after the intervention, approved by the Ethics and Research Committee (CEP) of PUC-SP (CAAE 89243518.8.0000.5482 and number of Opinion 2.693.574) and signing of the Free and Informed Consent Form. The sample was made up of 13 teachers from the Pontifícia Universidade Católica de São Paulo who took part in the course "Teacher, let's take care of your voice". This was offered as a distance learning course, divided into six modules that discuss voice care, vocal techniques, environment and work organization. Before the course started, the participants filled out a questionnaire for characterization, which included sociodemographic data and the instruments Voice Disorder Screening Index - VDI, Vocal Disability Index - 10 (VDI-10) and Vocal Fatigue Index - VFI, besides a questionnaire for Voice Knowledge Investigation (VCI-Pre). The latter was also filled out at the end of the course (ICV-Post), along with questions about the form and content of the course. Data were analyzed descriptively, by means of absolute (n) and relative (%) frequencies, measures of central tendency (mean, median) and dispersion (standard deviation, minimum and maximum values). For comparison between the two moments (pre and post) the Wilcoxon statistical test was applied, and the variable age underwent the Shapiro Wilk test (p≤0.05). RESULTS: More than half of the sample is female (7-53.8%), PhDs in their training (6-46.2%), with a workload between 31 and 40 hours a week (4-30.8%) and a mean age of 55.5 years. Of these teachers, 9-69.2% had no vocal handicap, 61.5% (8) failed the ITDV screening and as for vocal fatigue, the data indicate that teachers had fatigue and limitation, besides physical discomfort associated with voice, but they can recover their voice with vocal rest. The analysis at the end of the course showed that the knowledge about the voice of these teachers increased in all aspects, especially in resonance, articulation, posture and vocal care. According to the participants, the technology allowed them to receive the information and the content was transmitted in a clear and objective way, providing the teachers with the availability to be always present and have more time to perform other activities. CONCLUSION: the effects of the course "Teacher, let's take care of your voice", offered in remote and asynchronous modality, were positive once there was an increase in knowledge about all the aspects presented at the end of the course. This fact highlights the possibility of the course being offered to other interested parties, through the creation of a line of care in the institution where it was applied